P1 6 Excalibur: Sword of Promised Victory - Szczesniewski, Jakub; Humphrey, Lili-Mair; Jennings, John; Stainer, Alex (Physics Special Topics, 2024)
In this paper, we discuss the energy and intensity of the beam of light emitted by the sword Excalibur in Kinoko Nasu’s Fate series of works. The energy of the beam of light was found to be 9.4 ×1015 J and therefore the intensity of the light on perfectly absorptive surfaces is 1.1 ×1025 W m-2.